Edutaining audio: an exploration of education podcast design possibilities. Issue 1 (2nd January 2017) - Drew, Christopher
Abstract: The versatility, intimacy and ease of production of podcasting make it a logical technology to apply to flexible education contexts. As a result, there has been increasing scholarly interest in the value of education podcasting in recent years. While education podcasting literature has tended to explore podcast implementation in institutional contexts, education podcasts outside of academia have also grown in popularity, to the extent that "education" is a common sub-group in podcast aggregation sites. This paper adapts Fernandez, Sallan and Simo's framework of variables in education podcast design, to conduct a textual analysis of emergent design themes in non-institutional education podcasts. The findings reveal how highly successful podcasts from outside of educational institutions can both reinforce and challenge norms about education podcast design that exist within academic discourse, including in regard to podcast length, pedagogical approaches and the position of the podcast in the learning experience. It is the hope that the findings of this study might shift discourse from an interest in universalising ideas about "good practice" in education podcast design, towards more nuanced discussion of design practices that fit within specific contexts.